Unraveling the Impact of Job Stress, Work-Life Balance and Work Environment on Job Satisfaction: A Study on Malaysian Anti-Corruption Commission Investigation Officers - Izdihar, Abdul Faeez; Ab Latiff, Dilla Syadia; Yunus, Noor’ain Mohamad (Information Management and Business Review, 2023)
The study examines the challenges faced by Investigation Officers (IOs) at the Malaysian Anti-Corruption Commission, with an increasing number of cases impacting their job satisfaction. Despite this, there have been limited studies looking into how job stress, work-life balance, and work environment impact IOs’ job satisfaction. Thus, a study takes place to investigate the impact of job stress, work-life balance, and work environment on their satisfaction. Questionnaires were distributed to 164 respondents from MACC Headquarters in Putrajaya and MACC’s states’ offices and analyzed using SPSS V23. Multiple regression analyses were conducted and results showed a positive relationship between work-life balance and job satisfaction, and negative relationships between job stress and job satisfaction, as well as work environment and job satisfaction. The study recommends the MACC’s management team consider improvements in career paths, fair compensation, and rewards to enhance job satisfaction among IOs. It also suggests promoting better communication between IOs and the agency to address their needs and maintain a healthy work-life balance.